A new high-capacity and safe energy storage system: lithium-ion sulfur batteries. Issue 41 (9th October 2019) - Liang, Xin; Yun, Jufeng; Wang, Yong; Xiang, Hongfa; Sun, Yi; Feng, Yuezhan; Yu, Yan
Abstract : Lithium-ion sulfur batteries as a new energy storage system with high capacity and enhanced safety have been emphasized, and their development has been summarized in this review. Abstract : Lithium-ion sulfur batteries as a new energy storage system with high capacity and enhanced safety have been emphasized, and their development has been summarized in this review. The lithium-ion sulfur battery applies elemental sulfur or lithium sulfide as the cathode and lithium-metal-free materials as the anode, which can be divided into two main types. One is anode-type, where elemental sulfur is applied as the cathode, and the anode provides lithium ions. The other one is cathode-type, where lithium sulfide as the cathode provides lithium ions, and lithium-metal-free materials ( e.g., graphite, silicon/carbon) function as the anode. Recently, some new lithium-ion sulfur battery systems have also been proposed, and are discussed in this review as well. The lithium-ion sulfur batteries not only maintain the advantage of high energy density because of the high capacities of sulfur and lithium sulfide, but also exhibit the improved safety of the batteries due to a non-lithium-metal in the anode. This review paper aims to track the recent progress in the development of lithium-ion sulfur batteries and summarize the challenges and the approaches for improving their electrochemical performances, including the lithiation methods to prepare lithium-metal-free anodes in anode-type lithium-ion sulfur batteries and the lithium sulfide cathode modification approaches in cathode-type lithium-ion sulfur batteries. Furthermore, the challenges and perspectives for future research and commercial applications have also been enumerated.